Analysis of Parental Knowledge Dealing with Aspects of Toddler Parenting - Sunita,; , Poonam Malik (Archives of Current Research International, 2025)
Background: Parents play a pivotal role during the toddler years. Effective child-rearing practices during toddlerhood are essential for healthy development, shaping a child‘s cognitive, emotional and social growth. Research studies indicated that many parents lack crucial knowledge which can hinder their ability to provide optimal care. Objective: The objective of the present study is to examine the need of parents regarding knowledge on aspects of toddler parenting such as toddler growth aspects; toddler health; toddler nutrition; child care; toddler parenting; day to day parenting; toddler clothing and other products; toddler entertainment and education. Methodology: The present investigation was carried out in two cities of Haryana state i.e. Hisar and Fatehabad. The four healthcare centersof District Hisar and Fatehabad viz. i) Maharaja Agarsain Medical College (Agroha, Hisar), ii) Satija Health Care centre (Hisar), iii) Shree Balaji children Hospital and Maternity Home (Bhattu Kalan, Fatehabad) and iv) Jaipur Children Hospital (Fatehabad) were selected purposively. A total of 120 mothers of children aged 2-4 years, who visited the outpatient departments (OPD) of these hospitals, participated in the study. Data was gathered using a self-structured questionnaire. Findings: The results revealed that most mothers expressed a strong need for information on toddler growth and development, health, nutrition, childcare, parenting, clothing, products, and education. Conclusion: The study highlights a lack of awareness among women regarding various aspects of toddler parenting. Therefore, there is a clear need for further research to address the knowledge gaps among mothers of toddlers.